O nazwach pizzy w polskich lokalach gastronomicznych na tle kategorii glokalności - Tomasik, Piotr (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Artykuł poświęcony jest poszukiwaniu miejsca nazw pizzy w systemie onomastycznym. Autor rozważa stopień prioprialności badanych jednostek leksykalnych. Tłem analizy jest kulturowa kategoria glokalności.

The article is devoted to the localization of the names of pizza in the onomastic system. The author considers the degree of priopriality of studied lexical units. The background of the analysis is the cultural analysis of the glocality category.
On the names of the of pizza in Poland – against the background of the category of glocality
Keywords: onomastyka; nazwa własna; pizza; glokalność; onomastics; proper name; glocality